Measuring dysfunctional parenting: psychometrics of three versions of the Parenting Scale - Prandstetter, K; Waller, F; Heinrichs, N; Hutchings, J; Ward, CL; Danila, I; Lachman, JM; Foran, HM (Wiley, 2022)
Objective This study assessed the psychometric properties of three versions of the Parenting Scale (PS; original PS, 13-item version, and 10-item version) in three European middle-income countries.